Authentic Leadership on Employee Creativity: The mediating of Work Engagement - Yuliana Yuliana; Rini Sarianti (Universitas Negeri Padang, 2022)
This study analyzes: (1) the effect of authentic leadership on employee creativity (2) The effect of authentic leadership on work engagement (3) The effect of work engagement on employee creativity (4) The effect of authentic leadership on employee creativity through work engagement. This research is a quantitative research. The population in this study were the employees of the Regional Secretariat of Aceh Singkil Regency, amounting to 97 people. The sampling technique used was Total Sampling. Data obtained through a questionnaire with a Likert scale. The analysis technique used is through the SmartPLS software.3. The results of data processing in this study indicate that: (1) Authentic leadership has a positive and significant impact on employee creativity in the employees of the Regional Secretariat of Aceh SingkilRegency (2) Authentic leadership has a positive and significant impact on work engagement in the employees of the Regional Secretariat of Aceh Singkil Regency (3) Work engagement has a positive and significant impact on employee creativity in the employees of the Regional Secretariat of Aceh Singkil Regency (4) Authentic leadership has a positive and significant impact on employee creativity through work engagement in the employees of the Regional Secretariat of Aceh Singkil Regency.